Strengthening Teaching in "Rural," Indigenous-Serving Schools: Lessons From the Diné Institute for Navajo Nation Educators - Angelina E. Castagno; Marnita Chischilly; Darold. H. Joseph (Journal of Research in Rural Education, 2022)
This article reports on the first three years of a teacher-led professional development program on the Navajo Nation. We draw on both quantitative and qualitative data from our end-of-year surveys to highlight some of the early lessons we have gathered from the Diné Institute for Navajo Nation Educators (DINÉ). We highlight two guiding principles that have developed through this work, cultural responsiveness and teacher leadership, and we suggest that these guiding principles could be useful for other professional development efforts in Indigenous-serving contexts, many of which would be characterized as "rural." We connect these guiding principles to the broad concept of Native nation building, which situates teachers as frontline workers in Indigenous communities' efforts to engage self-determination through self-education. A key lesson from the DINÉ is that professional development for teachers in "rural" schools serving Indigenous students must aim to build capacity among teachers so they determine the ways in which local knowledge is integrated into curriculum and everyday practice.